Structural characterization of phosphatidylglycerol model membranes containing the antibiotic target lipid II molecule: a Raman microspectroscopy study - Sosa Morales, Marcelo Clemente (2017)
Effects induced by the incorporation of lipid II (LII) molecule into phosphatidylglycerol (PG) membranes were studied by Raman microspectroscopy. Spectral behavior of multilayer vesicles in liquid crystalline and gel phases formed by pure PG lipids and by PG/LII mixtures was evaluated. Differences shown by specific spectral markers of the lipid structure were associated with perturbations on the bilayer as response to the LII incorporation. Identification and interpretation of bands assigned to vibrations belonging to groups of the lipid polar region were supported by computational predictions. Quantum‐chemical calculations – B3LYP/6‐311++G(d,p) – were performed for a model charged molecule that mimics the PG lipid moiety in solvated state. Our Raman spectra demonstrate that the lipid phase is a determinant factor for both the bactoprenol tail penetration into the hydrophobic bilayer region and the perturbation degree at the membrane surface by the peptidoglycan moiety, because differential effects were observed for the two lipid systems studied. LII was able to penetrate the hydrophobic region of the lipid bilayer in the fluid phase, reaching the deep core and causing significant alterations in both the carbohydrate chain and the headgroup regions. By contrast, penetration of LII into a bilayer in the gel estate was restricted because of the high lipid packing that characterizes this phase. In this last case, interactions at the membrane surface were also indicative of partial interdigitating effect. Findings presented here provide valuable experimental evidence that contributes to the understanding of the mechanism by which lantibiotics recognize bacterial membranes.